Microbiome and Breast Cancer: New Role for an Ancient Population - Eslami-S, Zahra; Majidzadeh-A, Keivan; Halvaei, Sina; Babapirali, Fatemeh; Esmaeili, Rezvan (Frontiers in Oncology, 2020)
There are many risk factors associated with breast cancer (BC), such as the familial history of BC, using hormone replacement therapy, obesity, personal habits, and other clinical factors; however, all BC cases are not attributed to these risk factors. Recent researches show a correlation between patient microbiome and BC, which suggests that as a new risk factor. The present review article aimed at evaluating the role of the microbiome as a risk factor in the occurrence of BC, investigating the proposed mechanisms of interaction between the microbiome and human genes involved in BC, and assessing the impact of the altered composition of breast, gut, and milk microbiome in the physiological status of normal breast as well as cancerous or non-cancerous breast lesions. The study also evaluated the growing evidence that these altered populations may hinder chemotherapeutic treatment. The role of the microbiome in the development and maintenance of inflammation, estrogen metabolism, and epigenetic alterations was properly investigated. Finally, clinical and therapeutic applications of the microbiome- e g, probiotics, microbiome genome modulation, and engineered microbiome enzymes in the management of BC were reviewed.